2010
DOI: 10.1007/978-3-642-14712-8_4
|View full text |Cite
|
Sign up to set email alerts
|

Starfish on Strike

Abstract: This paper improves the price-performance ratio of ECM, the elliptic-curve method of integer factorization. In particular, this paper constructs "a = −1" twisted Edwards curves having Q-torsion group Z/2 × Z/4, Z/8, or Z/6 and having a known non-torsion point; demonstrates that, compared to the curves used in previous ECM implementations, some of the new curves are more effective at finding small primes despite being faster; and precomputes particularly effective curves for several specific sizes of primes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(43 citation statements)
references
References 8 publications
1
42
0
Order By: Relevance
“…On the other hand, the fastest scalar multiplication is obtained in [7] for a = −1 twisted Edward curves; as shown in [5], however, this limits the possibilities for interesting torsion groups (i.e., with cardinality greater than four) to Z/6Z, Z/8Z or Z/2Z × Z/4Z, thereby in particular excluding the two most profitable ones. For ECM the issue was settled in [4] where a = −1 twisted Edwards curves were compared to curves with E tors isomorphic to Z/12Z and Z/2Z × Z/8Z: it was found that the disadvantage of the formers' smaller torsion groups is outweighed by their faster scalar multiplication.…”
Section: Edwards Curves and Elliptic Curve Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the fastest scalar multiplication is obtained in [7] for a = −1 twisted Edward curves; as shown in [5], however, this limits the possibilities for interesting torsion groups (i.e., with cardinality greater than four) to Z/6Z, Z/8Z or Z/2Z × Z/4Z, thereby in particular excluding the two most profitable ones. For ECM the issue was settled in [4] where a = −1 twisted Edwards curves were compared to curves with E tors isomorphic to Z/12Z and Z/2Z × Z/8Z: it was found that the disadvantage of the formers' smaller torsion groups is outweighed by their faster scalar multiplication.…”
Section: Edwards Curves and Elliptic Curve Methodsmentioning
confidence: 99%
“…In [4] these are shown to be the curves −x 2 + y 2 = 1 − e 4 x 2 y 2 with e / ∈ {0, ±1}. Compared to generic e-values and averaging over the primes p of good reduction, [2] .…”
Section: Edwards Curves and Elliptic Curve Methodsmentioning
confidence: 99%
See 3 more Smart Citations